1997
DOI: 10.1017/s0007485300038670
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical mechanisms of organophosphate resistance inRhyzopertha dominica(Coleoptera: Bostrichidae) populations from the United States and Brazil

Abstract: Four possible biochemical mechanisms of organophosphate resistance were examined in populations of Rhyzopertha dominica (Fabricius) collected from eight locations in the states of Minas Gerais and Sao Paulo in Brazil and from seven locations in northeast Kansas, United States. Results from insecticide bioassays with synergists (triphenyl phosphate, diethylmaleate, and piperonyl butoxide) suggested that metabolic detoxification mechanisms might be involved in organophosphate resistance in some of the population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 20 publications
0
15
0
4
Order By: Relevance
“…This phenomenon is widespread among Coleoptera. For example, the Colorado potato beetle is resistant to imidacloprid (GraÞus and Bishop 1996, Olson et al 2000, Zhao et al 2000, pyrethroids, and organophosphates (Jiang et al 2010); Tribolium castaneum (Herbst) (Collins 1990), Listronotus maculicollis Kirby (Ramoutar et al 2009), and Sitophilus zeamais Motschulsky (Ribeiro et al 2003) are resistant to pyrethroids; and Rhyzopertha dominica (F.) is resistant to organophosphates (Guedes et al 1997). All of these insects had been highly exposed to insecticides, and their mean generation times are relatively short, as is also true for P. fuscipes (Bong et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is widespread among Coleoptera. For example, the Colorado potato beetle is resistant to imidacloprid (GraÞus and Bishop 1996, Olson et al 2000, Zhao et al 2000, pyrethroids, and organophosphates (Jiang et al 2010); Tribolium castaneum (Herbst) (Collins 1990), Listronotus maculicollis Kirby (Ramoutar et al 2009), and Sitophilus zeamais Motschulsky (Ribeiro et al 2003) are resistant to pyrethroids; and Rhyzopertha dominica (F.) is resistant to organophosphates (Guedes et al 1997). All of these insects had been highly exposed to insecticides, and their mean generation times are relatively short, as is also true for P. fuscipes (Bong et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Esses autores também testaram o sinergista DEF (S,S,S-tributilfosforotritioato) com deltametrina, nas mesmas populações de R. dominica, e não encontraram um efeito sinergista significativo, constatando que enzimas esterases possivelmente não estejam envolvidas na resistência a deltametrina em R. dominica. Guedes et al (1997a) demonstraram que a atividade específica da acetilcolinesterase diferiu significativamente entre populações resistentes e suscetíveis de R. dominica, indicando que a atividade aumentada da acetilcolinesterase parece estar associada com a resistência a organofosforados. E, com relação à resistência bioquímica aos piretróides, estudos de Collins (1990), com a espécie T. castaneum, indicam que o aumento do metabolismo enzimático na molécula do inseticida envolve oxidação e/ou hidrólise por ésteres.…”
Section: Palavras-chave Inseticidas Organofosforados; Inseticidas Piunclassified
“…Since then, resistance-modified AChEs have been described in many insect species [3-7]. Sequencing of the gene encoding AChE in resistant strains showed that the modifications arose from point mutations (Table 1).…”
Section: Introductionmentioning
confidence: 99%